1995
DOI: 10.1002/qre.4680110307
|View full text |Cite
|
Sign up to set email alerts
|

Off‐line quality control for V‐process castings

Abstract: In the present work Taguchi's approach has been applied to the V-process castings of Al-11 per cent Si alloy to acertain the most influential control factors which will provide better and consistent surface finish to the castings regardless of the noise factors present.The control factors of the V-process that may affect the quality of the castings are the molding sand, vibration frequency, vibrating time, degree of vacuum imposed, and pouring temperature.In order to understand how these factors affect the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…On the basis of this model, Singh and Singh (2011) studied the relationships between SH and controllable process parameters [14]. These relationships agree well with the trends observed by experimental observations made otherwise [8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…On the basis of this model, Singh and Singh (2011) studied the relationships between SH and controllable process parameters [14]. These relationships agree well with the trends observed by experimental observations made otherwise [8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 60%
“…The process uses a specially designed, strong, highly flexible polymer film to seal the open ends of the sand mould and form the mould cavity [8]. The literature review reveals that lot of work has been reported on optimization of VM process [9][10][11][12][13]. Various process parameters like: vibration frequency, pouring temperature and plastic film thickness for the sound casting produced by VM process have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The selected casting process parameters, along with their ranges, are given in Table 1. Experience reveals that non-linear behaviour of the parameters of a die casting process can be determined only if more than two levels are used [12]. Therefore, each parameter was analysed at three levels.…”
Section: Parameter Designmentioning
confidence: 99%
“…Dr. Genichi Taguchi has introduced several new statistical tools and concepts of quality improvement that depend heavily on the statistical theory of experimental design (Taguchi, 1998;Byrne and Taguchi, 1987). Some applications of Taguchi's methods in the foundry industry have shown that the variation in casting quality caused by uncontrollable process variables can be minimized (Johnston, 1989;Kumar and Gaindhar, 1995;Barua et al, 1997). The casting process has a large number of parameters that may affect the quality of castings.…”
Section: Introductionmentioning
confidence: 97%